Nicotiana spp. for the Expression and Purification of Functional IgG3 Antibodies Directed Against the Staphylococcus aureus Alpha Toxin - Opdensteinen, P.; Meyer, S.; Buyel, J. F. (Frontiers in Chemical Engineering, 2021)
Immunoglobulin subclass IgG1 is bound and neutralized effectively by Staphylococcus aureus protein A, allowing the bacterium to evade the host’s adaptive immune response. In contrast, the IgG3 subclass is not bound by protein A and can be used to treat S. aureus infections, including drug-resistant strains such as MRSA. However, the yields of recombinant IgG3 are generally low because this subclass is prone to degradation, and recovery is hindered by the inability to use protein A as an affinity ligand for antibody purification. Here, we investigated plants (Nicotiana spp.) as an alternative to microbes and mammalian cell cultures for the production of an IgG3 antibody specific for the S. aureus alpha toxin. We targeted recombinant IgG3 to different subcellular compartments and tested different chromatography conditions to improve recovery and purification. Finally, we tested the antigen-binding capacity of the purified antibodies. The highest IgG3 levels in planta (> 130 mg kg-1 wet biomass) were achieved by targeting the endoplasmic reticulum or apoplast. Although the purity of IgG3 exceeded 95% following protein G chromatography, product recovery requires further improvement. Importantly, the binding affinity of the purified antibodies was in the nanomolar range and thus similar to previous studies using murine hybridoma cells as the production system.